Improving Cognitive Learning Outcomes of Slow Learner Students Through Learning Strategies at SDI Al-Azhaar Tulungagung - 'Ilmi Dzanis Shulha, Irdla; Ja'far As-shodiq, Mohammad; Purwowidodo, Agus (LP2M UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
Slow learning is one type of learning problem or difficulty that often arises in elementary school. Slow learners are children who have intellectual potential slightly below normal but are not yet mentally disabled. So each learning activity takes longer than other children who have the same level of intellectual potential. This research aims to analyze and find teacher strategies for improving the learning outcomes of slow-learner students at SDI Al Azhaar Tulungagung. The approach used in this research is descriptive qualitative. The subjects in this research were the principal, the third grade teacher and the accompanying teacher. The data was collected using participant observation, documentation and in-depth interviews. The results of the research obtained at SDI Al Azhaar Tulungagung show that the teacher's strategy in improving the learning outcomes of slow learner students is there is an accompanying teacher as a therapist, one student and one accompanying teacher. Then provide resource centre classroom facilities, and special programs related to collaboration between schools by emphasizing control over students' food intake.